Determinants of GLC’s performance in Malaysia / Mohd Akram Mamat @ Ibrahim, Nor Syafiqah Syazwani Nordin and Wan Faizah Wan Tarmizi - Mamat @ Ibrahim, Mohd Akram; Nordin, Nor Syafiqah Syazwani; Wan Tarmizi, Wan Faizah (2015)
This study empirically investigates the factors determine the GLCs performance in Malaysia. It focuses on the determinants of GLCs performance measured by return on assets (ROA). Four variables are chosen as determinants namely government ownership, leverage, sales growth and profitability. The impact between-determinants of GLCs performance is conducted using panel static based regression which consists of pooled OLS regression, fixed effect and random effect model. The investigation of the study has been benefited from public listed companies in Bursa Malaysia spanning from 2005 to 2014. With 41 Government linked-companies as a sample, the findings of fixed effect regression model revealed that government ownership and leverage does have negative impact to firm performance except sales growth which is it does not give impact to firm performance. Meanwhile, profitability is the most significant factor that gives positively significant impact to firm performance.